How things work: the physics of everyday life - Bloomfield, Louis A. (New York, John Wiley Sons, Inc., 2001)
Written primarily for a one-term, undergraduate level course, this book attempts to convey an understanding and appreciation for the concepts and principles of Physics by finding them within specific objects of everyday experience. It's primary market are liberal arts students who are seeking a connection between science and the world they live in; among its many secondary markets are the growing number of institutions offering courses with scientific real-world context. These courses may also be offered to students from the Sciences, Engineering, Architecture, and other technical fields.
Appendix A-C, 469-475p.; Glossary 477-492p.; Index 503-512p.
Keywords: Physics